Isolated Nondominant Right Coronary Stenosis: Clinical Presentation and Management. (October 2013) - Ilia, Reuben; Cafri, Carlos; Wolak, Arik; Weinstein, Jean Marc
The frequency, clinical presentation, and management of severely stenotic isolated nondominant right coronary artery (NDRCA) have not been adequately defined. We sought to do so in a large cohort of patients undergoing coronary angiography. We retrospectively analyzed all patients who underwent coronary angiography in our institute between 1995 and June 2012, looking at those with a severe lesion in the NDRCA, recording demographic, clinical, and angiographic data. Of the 43 327 patients, 35 (0.08%) were found to have a severely stenotic NDRCA as a single-vessel disease. The most common indication for catheterization was acute coronary syndrome (49%). Most of the patients were managed conservatively (66%) and the entire group had a relatively benign course, with no coronary deaths. Severe stenosis of the NDRCA as isolated disease is a very rare entity, and although most commonly presenting with acute coronary syndrome, conservative management was the usual approach.